Neo-Mytho-Logic: Experience of Clarifying Modern Research Terminology - A. A. Zhitenev; E. S. Strelnikova (Научный диалог, 2022)
The question is raised about the terminological pluralism that exists in the paradigm of literary concepts related to the category of the mythological. The relevance of the study is due to the lack of differentiation in the interpretation of the concepts associated with the myth in the literature. Based on the totality of the considered studies, the authors propose their own version ofthe distinction between terms, which goes back to the specifics of the subject-object relations of the authorial and the mythological. The concepts of “myth”, “mythological”, “mythologism” and the processes of “demythologization” and “remythologization” associated with them are correlated with the logic of object domination over the level of the subject-author’s (personal) world-building intention. It is proved that the mythological in a work of art is characterized by structural and semantic isolation, as well as resistance to the influence of the individual author. It has been established that the formation of the neomythological, on the contrary, initially implies the aspiration of the author’s consciousness (subject) to build an artistic space in the logic of self-embodiment and axiologically oriented world-building. This determines the diversity of neomythological elements and the correlation of different cultural and philosophical layers, implicitly transformed by the author into neomyths, and it is proposed to define neomythologism not only as an artistic phenomenon, but also as a promising methodology for literary analysis. At the same time, the authors propose to distinguish between neo-mythological tendencies and the postmodern experience of creating “author’s myths”.